Fabrication of a highly dispersed/active Pd nanoparticle supported catalyst: a cation-assisted reduction method in ethylene glycol–water solution at mild temperature. Issue 6 (4th February 2020) - Xiang, Chunpeng; Xiao, Yanhua; Bai, Hang; Yin, Xia; Peng, Meng; Yang, Xiaojun; Ding, Yigang; Du, Zhiping
Abstract : Controllable and recyclable fabrication of a highly dispersed/active Pd/Al2 O3 -CARM catalyst at 50 °C by introducing M 2+ (M = Mn, Zn or Cu) ions to promote the reduction of Pd 2+ in ethylene glycol–water solution. Abstract : Development of sustainable routes to synthesize precious metal supported catalysts is of great importance because of their wide applications in the catalysis field. This paper reported a controllable and recyclable cation-assisted reduction route to fabricate a palladium nanoparticle supported catalyst. At 323 K, highly dispersed Pd/Al2 O3 -CARM was prepared through introducing M 2+ (M = Mn, Zn or Cu) ions to promote the reduction of H2 PdCl4 in ethylene glycol–water solution, and the residual filtrate after preparation could be recycled to prepare Pd/Al2 O3 catalysts. A turnover frequency of 300 × 10 2 h −1 was obtained for Pd/Al2 O3 -CARMn in solvent-free aerobic oxidation of benzyl alcohol to benzaldehyde.